Structure of dehydroquinate synthase reveals an active site capable of multistep catalysis. - Carpenter, E; Hawkins, A; Frost, J; Brown, K (1998)
Dehydroquinate synthase (DHQS) has long been regarded as a catalytic marvel because of its ability to perform several consecutive chemical reactions in one active site. There has been considerable debate as to whether DHQS is actively involved in all these steps, or whether several steps occur spontaneously, making DHQS a spectator in its own mechanism. DHQS performs the second step in the shikimate pathway, which is required for the synthesis of aromatic compounds in bacteria, microbial eukaryotes and plants. This enzyme is a potential target for new antifungal and antibacterial drugs as the shikimate pathway is absent from mammals and DHQS is required for pathogen virulence. Here we report the crystal structure of DHQS, which has several unexpected features, including a previously unobserved mode for NAD+-binding and an active-site organization that is surprisingly similar to that of alcohol dehydrogenase, in a new protein fold. The structure reveals interactions between the active site and a substrate-analogue inhibitor, which indicate how DHQS can perform multistep catalysis without the formation of unwanted by-products.